Do more birds mean more bird-aircraft collisions? A meta-analysis testing a key wildlife management tenet - Shane Guenin; Yue Liu; Bradley F. Blackwell; Travis L. DeVault; Esteban Fernández-Juricic (PLoS ONE, 2026)
Bird-aircraft collisions (bird strikes) pose threats to aviation safety and avian life. One of the tenets of airport-based management strategies to prevent bird strikes is the reduction of bird density within established separation distances from air operations areas. The rationale is that higher local bird densities could increase the spatial and temporal overlap in the use of airspace by both birds and aircraft, leading to a higher frequency of bird strikes. However, the strength and direction of this relationship have not been evaluated across published studies. This is an important gap, given how entrenched this assumed relationship has become to allocate limited resources to airport wildlife management. In this study, we assessed the strength of the relationship between avian abundance and bird strikes across studies using a meta-analytic approach. Through a reproducible literature search and screening criteria, we identified 20 outcomes (i.e., effect sizes) from 13 studies. We conducted a multilevel meta-analysis and found a positive correlation (Pearson’s r = 0.520, 95% confidence intervals: 0.308–0.683), supporting the positive relationship between bird abundance and bird strike frequency. We additionally found evidence that the existing literature has high levels of between-study heterogeneity and publication bias, low statistical power, and multiple methodological concerns. These issues suggest that our effect size estimation should be interpreted with care. Given the limitations of the published literature testing this relationship, we provide a set of methodological recommendations for improving future experiments. We call for prioritizing the empirical testing of the abundance-bird strike relationship on and near airports across the world, and the standardization of bird survey approaches. These future tests are key to aligning management efforts to local airport needs.